ANALISIS PENGARUH FAKTOR LOKASI, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUASAN PELANGGAN PRODUK ABON SAPI DI TOKO KL NOERIA SURAKARTA - Karina Noradilla Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The study was aimed to determine the factors that affect costumer satisfaction of side dish product (abon) at store KL Noeria Surakarta. The method used in this study is a survey method of data collection using questionnaires in Accidental Sampling Method with a number of respondents were taken as 50 people. The results showed that the Location Factor was not give affect for costumer satisfaction side dish product at store KL Noeria Surakarta. Even though, Service quality factor) and Price, significantly affect costumer satisfaction side dish product at store KL Noeria Surakarta. All factors contributed 45,6 percent of for costumer satisfaction side dish product at store KL Noeria Surakarta. Partially, the variables most affect positively and significantly to costumer satisfaction side dish product is service quality factor. Keywords: Location, Service quality, Price, Customer Satisfaction.